Article End of life care, Medicolegal Aspectsand Ethics in ICU: End of life care, Medicolegal Aspectsand Ethics in ICU (Bombay Hospital Journal, 2024)
: End of Life Care is one of the important quality measures of intensive care delivery. Towards the end of life, the focus of care must shift towards comfort and dignity in death. In the care of the dying, medical, ethical, socio cultural and legal aspects intersect. This chapter begins with a description of a real-life scenario where an end of life decision was made. It briefly touches upon the ethical underpinnings of foregoing of life support. It provides definition of terms used around terminal care. It goes on to provide guidance on the clinical pathway to end of life decision-making that includes Withdrawal, Withholding and Do Not Attempt Resuscitation orders. Legal developments in India are summarized and their practical application clarified